2000
DOI: 10.1016/s0735-1097(00)00830-5
|View full text |Cite
|
Sign up to set email alerts
|

Systolic anterior motion begins at low left ventricular outflow tract velocity in obstructive hypertrophic cardiomyopathy

Abstract: Systolic anterior motion begins at normal LVOT velocity. At SAM onset, though Venturi forces are present in the outflow tract, their magnitude is much smaller than previously assumed; the Venturi mechanism cannot explain SAM. These velocity data, along with shape, orientation and temporal observations in patients, indicate that drag, the pushing force of flow, is the dominant hydrodynamic force that causes SAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
131
1
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(145 citation statements)
references
References 37 publications
0
131
1
8
Order By: Relevance
“…However, subsequent studies have shown that accelerated flow around the septum produces a drag effect on an elongated and displaced mitral valve apparatus to ''push'' the leaflets into the outflow tract. 21,22 The dynamic nature of LVOT obstruction results from an amalgamation of changes in ventricular loading conditions and myocardial contractility that are sensitive to fluctuations in volume status, autonomic nervous activity, diurnal variation, pharmacotherapy, exercise, and even physical positioning during gradient assessment. 4,23 -26 The recognition of the variability of LVOT outflow tract gradient in clinical practice is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent studies have shown that accelerated flow around the septum produces a drag effect on an elongated and displaced mitral valve apparatus to ''push'' the leaflets into the outflow tract. 21,22 The dynamic nature of LVOT obstruction results from an amalgamation of changes in ventricular loading conditions and myocardial contractility that are sensitive to fluctuations in volume status, autonomic nervous activity, diurnal variation, pharmacotherapy, exercise, and even physical positioning during gradient assessment. 4,23 -26 The recognition of the variability of LVOT outflow tract gradient in clinical practice is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Through two-dimensional echocardiography, the SAM was revealed to begin before ejection, and slightly differentiated from the Venturi effect 16 . The obstruction is truly determined by the complex interaction between septum, mitral valve and flow vectors generated in ventricular cavity.…”
Section: Introductionmentioning
confidence: 99%
“…The position of the mitral valve leaflets in relation to the outflow tract is fundamental for the obstruction to develop 16 . The anterior displacement of papillary muscles and mitral subvalvar apparatus change the outflow tract geometry, reducing the respective area, favoring the contact between the anterior leaflet and the septum 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13) Possible explanations for this paradox include real observation of true hypercontractility in this disease entity, pseudo-normal contractility under the decreased left ventricular (LV) radial wall stress as a result of compensatory remodeling, 14,15) pseudo-vigorousness by favorable afterload reduction with complication of mitral regurgitation due to outflow obstruction, [16][17][18][19] or other unknown mechanisms.…”
mentioning
confidence: 99%